(3GdJehjd GdeUQaj deTQhYGJ GdHfjI GdCSGSjI HfXGe eTGQcI GdbWGY GdYGe hGdNGU (B/ s - (3UcHGf Ndjd QTjO GdTeQjs; (3gGfj UdGM SQj GdOjf s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3Cf OQGSI ehVhY (B((3GdJehjd GdeUQaj deTQhYGJ GdHfjI GdCSGSjI HfXGe eTGQcI GdbWGY GdYGe hGdbWGY GdNGU(B) (3dg CgejI cHjQI MjK GYJHQJ eTQhYGJ GdHfjI GdCSGSjI GdMO GdaGUd Hjf GdOhd GdeJbOeI hGdfGejI(B: (3hHJOGNdgG eY bWGYGJ CNQi ef CLd EfTGFgG dCfgG JJWdH OYekG cHjQkG(B: (3agj efXheI eJcGedI ef MjK GdJehjd hGdeTGQcI aj EfTGFgG ef CTNGU GdbWGY GdYGe hGdNGU(B: (3MjK JfWhj JMJgG YOI YbhO hGJaGbjGJ hCTNGU(B: (3HeYfi Cf dOjgG YdGbGJ eJTYHI heNJdaI heJYOOI JJOGNd aj eG HjfgG ef CLd GfTGFgG, hJfGhdJ GdOQGSI eaghe GdLgGR GdeUQaj heGgjI eTQhYGJ GdHfjI GdCSGSjI heQGMd JWhQgG, hHMKJ GdOQGSI GjVG aj GdOhQ GdJehjdj ddLgGR GdeUQaj deTQhYGJ GdHfjI GdCSGSjI, HGdGVGag Gdi GdBKGQ GdeJQJHI Ydi eTQhYGJ GdHfjI GdGSGSjI hcjajI JhRjYgG(B: (3hJWQbfG Edi YQV HYV GdJLGQH GdeMdjI hGdOhdjI(B: (3hCNjQkG JVefJ fgGjI OQGSJfG Ydi cjajI GfJgGA eTQhYGJ GdHfjI GdGSGSjI hJShjI GdefGRYGJ ajgGs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2015s
(3HHdjhLQGajG(B: (3UaMGJ (B296-325s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdYGes; (3GdJWhQ GdJGQjNj ddLgGR GdeUQajs; (3eTQhYGJ GdHfjI GdGSGSjIs; (3Gdgjcd GdJfXjej ddLgGR GdeUQajs; (3eQGMd JWhQ GdHfjI GdGSGSjIs; (3UhQ GdJehjd GdeUQajs; (3eaghe GdJehjd GdeUQajs; (3OhQ GdLgGR GdeUQaj aj Jehjd eTQhYGJ GdHfjI GdGSGSjIs; (3YbhO GdTQGcI Hjf GdbWGYjf GdYGe hGdNGUs; (3Gdgjcd GdJfXjej deTQhYGJ GdHfjI GdGSGSjIs; (3eNGWQ eTQhYGJ GdHfjI GdGSGSjIs; (3GfJgGA eTQhYGJ GdHfjI GdGSGSjIs; (3JShjI GdefGRYGJ GdfGTFI Yf JfajP YbhO GdTQGcIs; (3WQb GdeTGQcI Hjf GdbWGYjf GdYGe hGdNGUs; (3GdJfHD HGdeNGWQ GdeUQajIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes